Properties of Infinite Matrices and Sequence Spaces - Sahani, Suresh Kumar; Tiwari, S.K. (Darul Yasin Al Sys, 2023)
Some general theorems on the product of matrices and their applications to infinite series have been obtained. All theorems include, as special cases, a set of well-known results. Several specific new results can also be deduced from it.